EFEKTIVITAS MEDIA FLIPBOOK BERBASIS MODEL STAD TERHADAP HASIL BELAJAR SISWA KELAS V: EFEKTIVITAS MEDIA FLIPBOOK BERBASIS MODEL STAD TERHADAP HASIL BELAJAR SISWA KELAS V - Andriyani Afliyanti Dua Lehan; Markus Sampe; Sofia G. Un Lala; Ribob Petrus Mooy (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
ABSTRACT This research is a quantitative research that aims to determine the effectiveness of the STAD Model-Based Flipbook media on the learning outcomes of grade V students. The population of this study is grade V students of SD Negeri Oebali for the 2022/2023 school year, totaling 11 people, using saturated sampling techniques so that all populations are used as research samples. This study used observation sheets and tests as a type of instrument with data collection techniques such as observation, tests, and document studies. Based on the results of the normality test of learning outcomes from the pretest-posttest, a significant value of 0.984 > 0.05 was obtained so that the data was normally distributed, the homogeneity test results showed (sig) Levene's of 0.055 > 0.05 so that the data obtained were homogeneous. The results of hypothesis testing, using paired sample t-test show that the value of sig. (2-tailed) from pretest and posttest values of 0.000 < 0.05 thus it can be concluded that flipbook media based on the STAD model is effective in improving student learning outcomes. Keywords: learning outcomes, media flipbook, STAD model